2020
DOI: 10.1186/s12884-020-2825-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal omentin-1 level, quality of life and marital satisfaction in relation to mode of delivery: a prospective cohort study

Abstract: Background: The purpose of this study was to evaluate the maternal omentin-1 level, quality of life and marital satisfaction of women with cesarean and vaginal delivery. Methods: This prospective cohort study was conducted on 45 women with elective cesarean delivery and 45 women with vaginal delivery who referred to a public hospital in Tehran, Iran. Maternal omentin-1 level was measured by ELISA kits within 24 h after delivery. The maternal quality of life and marital satisfaction in the third trimester of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…We previously reported the demographic and clinical characteristics of participants. 18 Based on the results of our study, the serum leptin level was significantly higher in NVD group compared to CS group (mean AE SD in NVD group 49.45 AE 24.00 vs. 39.89 AE 15.45 ng/mL in CS group; p = 0.033). The serum adiponectin level in CS group was not significantly different from NVD group (p = 0.232) (Figure 1).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…We previously reported the demographic and clinical characteristics of participants. 18 Based on the results of our study, the serum leptin level was significantly higher in NVD group compared to CS group (mean AE SD in NVD group 49.45 AE 24.00 vs. 39.89 AE 15.45 ng/mL in CS group; p = 0.033). The serum adiponectin level in CS group was not significantly different from NVD group (p = 0.232) (Figure 1).…”
Section: Resultsmentioning
confidence: 55%
“…Considering the rapid rise of CS rate worldwide, our study aimed to investigate the difference between maternal adiponectin and leptin levels and their gene expression at birth, maternal BMI, and breastfeeding duration at 24 months postpartum depending on the mode of delivery. Indeed, this study is a follow‐up of our previous study, where results have been reported elsewhere 18 . We released these findings late because the results of adiponectin and leptin levels and their gene expression were not ready when the first paper was submitted, and we also needed more time to determine the postpartum BMI as well as lactation duration.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…(Parvanehvar, Simin, et al, 2020) [19] 45 women with elective cesarean delivery and 45 women with vaginal delivery from a public hospital in Iran Women after spontaneous vaginal delivery have a better quality of life than women after caesarean section as dimension on physical, mental, emotional, environmental, and social aspects…”
Section: Resultsmentioning
confidence: 99%
“…During pregnancy, there are changes in the body's metabolism to meet the needs created by the increase in breast and genital tissue itself and the growth of the fetus and after birth [23]. The results of the cohort study showed that women who gave vaginal birth had higher omentin-1 levels than women who underwent caesarean section [19]. Omentin-1 is an adipokine produced mainly in adipose tissue, has anti-inflammatory, anti-bone loss, and insulin-sensitizing effects [24]- [26].…”
Section: Discussionmentioning
confidence: 99%